Bacterial production of transparent exopolymer particles during static and laboratory-based cross-flow experiments. Issue 2 (5th February 2016) - Jamieson, Tamar; Ellis, Amanda V.; Khodakov, Dmitriy A.; Balzano, Sergio; Hemraj, Deevesh A.; Leterme, Sophie C.
Abstract : The aim of this paper was to provide novel insights into the biofouling mechanism of transparent exopolymer particles (TEP) production through the use of static and laboratory-based cross flow experiments. Abstract : Biofouling of seawater reverse osmosis (SWRO) membranes represents one of the leading causes of performance deterioration in the desalination industry. This work investigates the biofouling potential of microbial communities present in a reverse osmosis (RO) feed tank. As an example, water from the RO feed tank of the Penneshaw desalination plant (Kangaroo Island, South Australia) was used in a static biofilm formation experiment. Cultures of the indigenous biofilms formed during the static experiment showed that α-Proteobacteria and γ-Proteobacteria accounted for nearly 80% of the classes of bacteria present in the RO feed tank. Pseudomonas sp. was identified as the major species and isolated for testing in static and laboratory-based cross flow biofilm formation experiments. Results showed that the volume of TEPs generated by Pseudomonas sp. during the laboratory-based cross-flow experiment was 10 fold higher to that produced during the static experiment for the same time period, while both experiments were inoculated with cell concentrations of the same order of magnitude. The availability of nutrients was also shown to be a key driver in TEP production, particularly for the static experiments. This study provides insights into the phenomenon of biofouling by assessing the production of biofouling precursors from one of the main genera of biofilm-forming bacteria, namely Pseudomonas sp.